The Physiological Effects of Whole-Body Vibration Combined with Other Exercise Modalities in Overweight and Obese Individuals: A Systematic Review - Daniel Batouli-Santos; Ana Carolina Coelho-Oliveira; Vanessa Amaral Mendonça; Alexei Wong; Adérito Seixas; Ana Cristina Rodrigues Lacerda; Anelise Sonza; Ayman Alhammad; Mario Bernardo-Filho; Danúbia da Cunha de Sá-Caputo; Redha Taiar (Biology)
Introduction: Emerging evidence indicates that whole-body vibration (WBV) may be a relevant adjunct in interventions targeting overweight and obese individuals. Moreover, WBV has been applied in combination with other exercise modalities and therapeutic strategies, with various physiological responses observed in this population. Objective: The current systematic review aimed to assess the physiological effects of WBV with other modalities of exercises in overweight and obese individuals. Methods: Searches in PubMed, Embase, Web of Science, Scopus, and Cochrane databases were conducted to assess physiological responses to the combination of WBV with other modalities of exercises in overweight and obese individuals. Publications were identified and the screening was performed by two reviewers, independently. Irrelevant studies were excluded based on the eligibility criteria. Results: Seven studies, analyzing different outcomes, were included, with a mean methodological quality score of 7. Four studies analyzed the acute effect and three studied the cumulative effect, with different intervention protocols. Increases in growth hormone (GH) concentrations and bioelectrical phase angles, and reductions in fat mass, blood triglycerides, and cholesterol concentrations, as well as blood pressure, heart rate, and arterial stiffness, were reported. Conclusions: WBV combined with other exercise modalities seems to promote important physiological responses in overweight and obese individuals. However, more large-scale, long-term randomized controlled trials with WBV and other modalities of exercises in overweight and obese cohorts are needed to corroborate and expand the findings of the current systematic review.